A desmistificação dos estereótipos do turismo na esfera acadêmica: um estudo a partir da percepção dos alunos da universidade federal do Rio Grande do Norte(UFRN) - Santos, Geovana Flávia dos (2025)
This study deals with stereotypes in the academic sphere and aims to analyze the stereotypes created about the Tourism course, based on the perception of undergraduate Tourism students at the Federal University of Rio Grande do Norte, pointing out how these stereotypes influence their academic training. This is an exploratory-descriptive study with a qualitative approach. Data was collected by means of an online questionnaire using Google forms, with open questions, totaling 37 respondents. A coding process was used for data analysis, which culminated in five main codes that summarize the stereotypes related to the course: association with travel; association with hotels; association with tour guides; perception that the job market in the area is devalued; and perception that the course is not relevant. The main results obtained during the research show that, most of the time, students feel the influence of stereotypes during their academic training, and that these have a negative impact, generating discouragement both in relation to the course and in relation to the students.